Pengaruh Keaktifan Belajar, Kemandirian Dan Kreativitas Terhadap Prestasi Belajar Matematika Siswa Kelas IX SMP - Aisyah Hariyani Achmad; Muhammad Dinar; Bernard (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study was ex-post facto research, which purposed to know the influences of learning activeness, independence and creativity toward Students’ Mathematics Learning Achievement on grade IX of SMP. Sample of study was chosen randomly three class from nine classes. Data were collected using the questionnaires and test learning achievement. The data were analyzed by Descriptive andInferential. Descriptive analyze obtain (1) Students’ mathematics learning achievement are at high category, (2) Learning activeness are at high category, (3) Learning independence are at high category, (4) Learning creativity are at low category. Inferentially acquire (1) There is influences of learning activeness, learning independence and learning creativity together towards students’ mathematicslearning achievement, (2) There is a positive influence of learning activeness toward students’ mathematics learning achievement by paying attention to the learning independence and learning creativity, (3) There is a positive influence of learning independence toward students’ mathematics learning achievement by paying attention to the learning activeness and learning creativity, (4) There was no influence of learning creativity toward students’ mathematics learning achievement by paying attention to the learning activeness and learning independence.